2013
DOI: 10.1093/intimm/dxt059
|View full text |Cite
|
Sign up to set email alerts
|

Controlling immune responses by targeting antigens to dendritic cell subsets and B cells

Abstract: Delivering antigens in vivo by coupling them to mAbs specific for unique receptors on antigen-presenting cells (APCs) is a promising approach for modulating immune responses. Antigen delivery to receptors found on myeloid dendritic cell (DC) subsets, plasmacytoid DCs and B cells has shown them all to be viable targets to stimulate either the cellular or humoral arms of the immune system. It is now evident that antigen-targeting approaches can also be used to invoke antigen-specific inhibition of immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…Our results thus far suggest BDCA2-mediated tolerance induction may operate via a distinct mechanism compared to what occurs after Ag targeting to other receptors (1). Ag delivery to DEC205 on CD8α + DCs, when administered in low doses in the absence of adjuvant, induces CD4 + T cell tolerance mediated by de novo induction of T reg cells (48).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our results thus far suggest BDCA2-mediated tolerance induction may operate via a distinct mechanism compared to what occurs after Ag targeting to other receptors (1). Ag delivery to DEC205 on CD8α + DCs, when administered in low doses in the absence of adjuvant, induces CD4 + T cell tolerance mediated by de novo induction of T reg cells (48).…”
Section: Discussionmentioning
confidence: 71%
“…It was recently shown that binding of mAbs to the transferrin receptor redirects its native intracellular trafficking (i.e., when bound by its natural ligand, transferrin) from recycling endosomes to late endosomal compartments (61). The extent to which mAb binding affects the internalization pathways of receptors such as BDCA2 and Siglec-H is not known and may be one factor that contributes to the differences in outcomes following targeting Ag to different receptors on pDCs (1). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their potent capacity to capture, process, and present Ag to T cells, Ag-targeting studies have focused on subsets of DCs and improved CTL responses against tumors [3][4][5][6][7][8]. More recently the induction of humoral immunity via Ag targeting to DC subsets has gained renewed interest [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Since the disentanglement of the heterogeneity of different APC subtypes, their specific targeting paved the way towards fundamental research on the exact therapeutic role of each APC subset in antitumor immunotherapy. Moreover, DC subtype specific targeting has already been reported for CLEC9A/BDCA-3 (murine/human cDC1), DCIR-2 (murine cDC2), BDCA-2 (human pDCs), SiglecH and BST2 (murine pDCs), and langerin (LCs) and showed promising differences in the elicited immune responses as a reflection of the specific function of these DC subtypes in situ [11,81,[131][132][133][134][135]. However, DC subset specific functions are not fixed but vary among several factors such as species and inflammatory state.…”
Section: Is Targeting a Step Forward In Vaccine Development?mentioning
confidence: 99%